Executive succession: The changing of the guard at the top of the golden arches food chain. A case study of top leader succession in global fast food giant McDonalds. - Giles, Joe (2017)
The study examines the role of successor origin on CEO’s post succession performance through the use of a case study to unpack the succession events of McDonalds, with the aim of providing deeper insight and understanding into the successor origin phenomenon and the underlying factors affecting post succession performance. Based on the latest two CEO succession events at McDonald’s with an inside successor, Don Thompson and an outside successor, Steve Easterbrook out evidence challenges previous literature and theory around the success of both inside and out outside CEO’s. With a particular focus on why such performance occurred during each CEO’s tenure, considering inside successor ability to maintain strategic continuity and an outside successor ability to initiate strategic change, the case aims to shed light on how each successor reacted to the specific context of the succession event. Whilst also considering a number of underlying factors outside of successor origin that impact a CEO’s post succession performance, the study provides evidence supporting the need for a finer grained classification on successor origin.